Antioxidant Activities and Phytochemicals of Leaf Extracts from 10 Native Rhododendron Species in Taiwan. (2nd June 2014) - Lin, Chi-Yang; Lin, Lei-Chen; Ho, Shang-Tse; Tung, Yu-Tang; Tseng, Yen-Hsueh; Wu, Jyh-Horng
Abstract : Rhododendron, one of the most famous ornamental plants in the world, is traditionally a medicinal plant. However, the potential bioactivities of native Rhododendron in Taiwan have not been completely studied. In this study, the results revealed that Rhododendron pseudochrysanthum exhibited the best antioxidant activities among 10 native Rhododendron species in Taiwan. Furthermore, based on a bioactivity-guided isolation principle, nine specific phytochemicals were isolated and identified as (2 R, 3 S )-catechin (1 ), (2 R, 3 R )-epicatechin (1 ′ ), (2 R, 3 R )-dihydromyricetin 3- O - β -l -arabinopyranoside (2 ), (2 S, 3 S )-taxifolin 3- O - β -l -arabinopyranoside (2 ′ ), (2 R, 3 R )-taxifolin 3- O - β -l -arabinopyranoside (3 ), myricetin 3- O - β -d -glucopyranoside (3 ′ ), rutin (4 ), hyperoside (5 ), and quercitrin (6 ). Of these compounds, 2 and 3 were found to be major bioactive compounds, and their concentrations in the n -butanol (BuOH) fraction were determined to be 52.0 and 67.3 mg per gram, respectively. These results demonstrated that methanolic extracts of Rhododendron pseudochrysanthum leaves have excellent antioxidant activities and great potential as a source for natural health products.